Graphene/semicrystalline-carbon derived from amylose films for supercapacitor application - Deraman, M; Sazali, NES; Hanappi, MFYM; Tajuddin, NSM; Hamdan, E; Suleman, M; Othman, MAR; Omar, R; Hashim, MA; Basri, NH; Nor, NSM; Dolah, BNM; et al. (IOP Publishing Ltd, 2024)
Indexed by WOS/Scopus